Establishing Sustainable Cardiothoracic Surgery Programs in Underserved Countries - Fenton, Kathleen; Cardarelli, Marcelo; Molloy, Frank; Novick, William (The Thoracic and Cardiovascular Surgeon, 2018)
Congenital heart disease is the most common birth defect worldwide, and accounts for a high proportion of the world's infant mortality. About 9 of every 10 babies born each year are born in areas without adequate access to heart surgery; overcoming this problem will necessitate addressing the worldwide shortage of an estimated 3,700 pediatric cardiac surgeons. Establishing sustainable heart surgery programs requires more than an investment of money: political, social, and cultural issues unique to each environment need to be addressed. Organizations desiring to help develop cardiac surgical centers need to focus on communication and bidirectional education, and to make a long-term commitment to each site. By identifying and addressing obstacles, success rates are high.
Keywords: congenital heart surgery; developing countries; humanitarian